Process Evaluation of Immunization Component in Mamta Diwas and Support Services in Kheda District, Gujarat - Sharma, Deepak Kumar; Varun, Arun; Patel, Rakesh; Singh, Uday Shankar (National Journal of Community Medicine, 2013)
Background: Mama Diwas is a fix day, fix site, preventive, promotive health care service center for mother and child. Objectives: The present study is to evaluate the process of Mamta Diwas in terms of different immunization variables and the logistic support to Mamta Diwas from Primary Health Centre. Methods: The present study is a “Descriptive cross sectional study” encompassing all the PHCs in Kheda district. The Mamta Diwas checklist is used a tool for the data collection. Results and: Forty (80%) had calculated the beneficiaries for the year and based on it only 17(34%) have calculated the logistics requirement. In 45 PHCs T-series vaccine and Hepatitis- B (Hep-B) vaccine were not found at the bottom of the Ice lined Refrigerator(ILR). In 11(22%) PHCs, dropout rate was found to be more than 10%. Adverse events following immunization (AEFI) were reported from 20(40%) PHCs and Vaccine Preventable Diseases (VPD) were reported from 25(50%) PHCs. Information Education and Communication (IEC) materials were displayed in 38(76%) PHCs. In 41(82%) session sites, time of reconstitution was mentioned on the vial. Site of vaccination and correct dosage and technique of vaccination was known to every interviewed Female Health Worker (FHW) at all the session sites. Conclusions: Programme management at PHC needs to be emphasized. Vaccine storage practices and cold chain maintenance is up to the mark throughout the District.